2018
DOI: 10.1159/000496206
|View full text |Cite
|
Sign up to set email alerts
|

miR-192 Is Overexpressed and Promotes Cell Proliferation in Prostate Cancer

Abstract: Objective: Prostate cancer (PCa) is one of the most prevalent types of cancer among men worldwide. The incidence of PCa is increasing in China. Therefore, there is an urgent need to identify novel diagnostic and prognostic markers for PCa to improve the treatment of the disease. Methods: The Cancer Genome Atlas (TCGA) and GEO database were used to analyze the expression of miR-192, and the relationship between miR-192 and the clinical features of patients with PCa. Cell cycle and cell proliferation assay were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 27 publications
2
16
0
Order By: Relevance
“…Moreover, tissue-derived and serum-exosomal expression of miR-192-5p could discriminate between PDAC and HCs with good accuracy, similar to that of established tumor marker CA.19-9. However, the clinical value of miR-192-5p remains ambiguous, as previous studies investigating its regulation in PDAC revealed in part contradictory results ( Table S1 [ 27 , 28 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ]). For the first time in 2013, Zhao et al described an overexpression of miR-192-5p in tumor tissue and blood serum of PDAC patients [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, tissue-derived and serum-exosomal expression of miR-192-5p could discriminate between PDAC and HCs with good accuracy, similar to that of established tumor marker CA.19-9. However, the clinical value of miR-192-5p remains ambiguous, as previous studies investigating its regulation in PDAC revealed in part contradictory results ( Table S1 [ 27 , 28 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ]). For the first time in 2013, Zhao et al described an overexpression of miR-192-5p in tumor tissue and blood serum of PDAC patients [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, decreased levels of circulating miR-192-5p were shown to correlate with presence of bone metastasis in non-small cell lung cancer (NSCLC) [ 37 ]. Contrarily, its upregulation in tissue of esophageal squamous cell carcinoma, prostate cancer, and nasopharyngeal carcinoma illustrated the different tumor specific signatures of miR regulation [ 38 , 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another miRNA, whose participation in different types of human tumors has been well-established in numerous studies is miR-192 (28)(29)(30). Notably, in the present study, we found that the expression of miR-192 was significantly decreased only in the breast cancer tissues, but not in the serum.…”
Section: Discussionmentioning
confidence: 99%
“…Also, miR‐192 was upregulated in high‐grade prostate cancer compared to low‐grade. In addition, the upregulation of miR‐192 was associated with a shorter biochemical recurrence‐free survival time 124 . Furthermore, miR‐215 was upregulated in tissues of high‐grade prostate cancer 125 .…”
Section: Mir‐192 Family As a Cancer Diagnosis Prognosis And Therapementioning
confidence: 98%
“…In addition, the upregulation of miR-192 was associated with a shorter biochemical recurrence-free survival time. 124 Furthermore, miR-215 was upregulated in tissues of high-grade prostate cancer. 125 However, it was observed that the expression of miR-215 in prostate cancer AT1 cell line and rat model was downregulated by extracellular acidosis and represented that pH may affect the biological behavior of tumors via miRNAs.…”
Section: Prostate Cancermentioning
confidence: 99%